Analisis penerapan tax planning sebagai upaya penghematan pajak penghasilan pasal 21 PT Parwata Kencana Abadi Manado - Moniaga, Maura Agustin Angelica; Sondakh, Jullie J.; Lambey, Robert (Yayasan Widyantara Nawasena Raharja, 2025)
Tax Planning is one of the methods used by taxpayers to save taxes. Tax planning is used to anticipate tax evasion. Through tax planning, PT Parwata Kencana Abadi needs to make efforts that can help pay taxes more efficiently and help the process of calculating taxes on the company's employee income. This study aims to determine how Tax Planning is analyzed as an effort to save income tax article 21 at PT Parwata Kencana Abadi using these methods. Based on the results of the study, it was concluded that it is more efficient to pay taxes using the Gross Up method, compared to the other two methods. Because in the Gross Up method, the company PT. Parwata Kencana Abadi will provide tax benefits that are the same as Article 21 Income Tax deducted from employee income. By implementing the Gross Up method, it also affects the company's income tax burden and net profit due to the additional tax benefits that reduce the company's income payable.